Marx's Ecology : Materialism and Nature - Foster, John Bellamy (Book collections on Project MUSE., 2000)
The author examines the writing of Marx and others, and "by reconstructing a materialist conception of nature and society, Marx's ecology challenges the spiritualism prevalent in the modern Green movement, pointing toward a method that offers more lasting and sustainable solutions to the ecological crisis."--Cover